The Antagonism Hypothesis: A New View on the Emergence of Consciousness - Weirui Xiong; Lu Yu (Brain and Behavior)
ABSTRACT Purpose The generation of consciousness poses a complex scientific challenge. Neuroscience and biological sciences have extensively studied this phenomenon, yielding numerous theories and hypotheses. However, to date, no reliable evidence has emerged to exclude any hypothesis conclusively, nor has any theory garnered unanimous agreement. This study aims to offer novel insights for further in‐depth study on consciousness. Method A new theoretical hypothesis was proposed based on reviews and comments from predictive processing theory, information theory, thermodynamics, and neuroscience. Findings This study argues that, first, it is necessary to clarify that the core implication of the concept of consciousness is first‐person perception. Accordingly, the study of consciousness is based on this premise. Second, on this basis, the antagonistic hypothesis of consciousness generation was proposed. This hypothesis holds that consciousness arises from the antagonism of mature individual experiences that cannot be seamlessly integrated with the function of addressing and navigating these conflicts. Conclusion The antagonism hypothesis is a new concept regarding the generation of consciousness that deserves further study.